Self-gripping polyester mesh with absorbable polylactic acid microhook versus polypropylene mesh for open inguinal hernioplasty - Sindhal, Minesh L.; Choksi, D. B.; Sarkar, Arnab; Sutariya, Akshay (International Surgery Journal, 2018)
Background: Inguinal hernias are frequently encountered disease. The hernia surgery has gone through a major evolution from Bassini’s heralding of the modern era to today’s mesh-based open and laparoscopic repair. The Purpose of this study is to compare clinical outcomes following sutureless repair with Self gripping polyester mesh incorporating absorbable polylactic acid microhook (Progrip) to traditional Lichtenstein repair with polypropylene mesh secured with sutures for open inguinal hernioplasty. Methods: 60 patients with diagnosis of inguinal hernia underwent open hernioplasty, after being randomized into two groups, one half of them using Progrip mesh and other group, using Polypropylene mesh over a period of one year at Department of General Surgery at Sir Sayajirao Gaekwad (SSG) Hospital, Baroda. Operative data were recorded, and the patients were followed-up accordingly. Independent assessors were assigned to obtain post-operative pain scores, other secondary outcomes. Results: The present study concluded that Self gripping mesh (ProgripTM) repair is superior to Polypropylene mesh in short term outcomes and in certain long-term outcomes like chronic groin pain. Conclusions: Open Inguinal hernioplasty using Self Gripping mesh (Progrip) mesh has better outcome in terms of operative time, post-operative pain, hospital stay, early return to professional life, and chronic pain.